(untitled) (Jurnal kesehatan komunitas (Journal of community health), 2026)
Music therapy is a non-pharmacological intervention that is increasingly recognized as effective in reducing anxiety and discomfort during pregnancy. It is a structured and purposeful approach conducted by trained professionals to support physical and psychological well-being. Music therapy can be applied actively, such as singing or playing instruments, or passively by listening to music, including classical music. This literature review used three databases: PubMed, Google Scholar, and ScienceDirect. Articles published between 2021 and 2025 were selected and accessed from May 10 to May 28, 2025. The search used the keywords “Classical Music,” “Anxiety,” and “Pregnancy.” From an initial 1,108 articles, four research met the exclusion and inclusion criteria and were reviewed. The results indicate that classical music therapy is effective in reducing anxiety and stress levels in pregnant women. Overall, music therapy provides significant physical and psychological benefits, helping to improve comfort and emotional well-being during pregnancy. Therefore, classical music therapy is recommended as a safe, holistic, and non-pharmacological approach in prenatal care to support maternal well-being.